Phylogenetic and bottleneck analysis of the Turkish Arabian and Thoroughbred horse populations - Yarali, Cevdet; Koseman, Abdurrahman; Ozsensoy, Yusuf; Seker, Ibrahim; Toprak, Burhan; Zengin, Kemal (Univ Zulia, Facultad Ciencias Veterinarias, 2023)
This study aimed to determine the phylogenetic and bottleneck analyses of Turkish Thoroughbred and Arabian horse populations. In the study, genotyping was performed using a total of 17 microsatellite markers in the samples taken from 959 Thoroughbred and 813 Arabian horses. The average effective allele number in Arabian horses was 3.338 and the average number of alleles was 7.412 in Thorougbred horses. Genetic distance and genetic identity between Thoroughbred and Arabian breeds was 0.411 and 0.663, respectively. Also genetic identity in each Arabian and Thoroughbred horse populations was 1.000. The FCA table showed that the two breeds were completely separated from each other and were compatible. In conclusion; the bottlenecks of Thoroughbred and Arabian horse populations were in a normal L distribution and these horse breeds do not appear to have succumbed to introgression. Therefore, they are not yet at risk of extinction any time soon.
Análisis filogenético y de cuello de botella de las poblaciones de caballos Turcos Árabes y de Pura sangre
Keywords: Arabian horse; bottleneck; microsatellite; phylogenetic analysis; thoroughbred horse